Evaluation du respect de calendrier vaccinal chez les enfants pygmées en âge de 0-59 mois - ZANIWE, Félix-Amand FUFULAFU; WOWO, Innocent BULUPIY (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
The topic of our researh or study is entitled « The Evaluationof the observance of the pygmy children’s vaccinal calender in the uebanand rural health area/ zone of Isiro. Vaccination has a considerable impact on infantile morbility and mortality. Millions of enfants continue dyng every year because of vaccination avoidable diseases (by vaccination). In France, almost  23.5 millions of thidren are no always vaccinated completely every year  due tho the lack of vaccine, two millions of enfants  die in countries in positionof devellopmentt of vaccination avoidablee deseases (USAIDet al ,2006). In isiro town and its surrondingswe have noticed that certain pygmey children aged of  0to 11 monthshave no access to different antigins of  routine PEV : (Elarged vaccine program).Taking into account what goos above, te following questions are to by asked :What  would be the proportion of pygmy children who respect the vaccinal calender ?What would be the factors hyndering  the observance of the vaccinalcalendar  on the port of these children ?What could  be the strategees  susceptibles to increase the vaccinal acces  in the children ?  to the reach these results .The following objectives have been fixes :To determine the proportion of pygmy infants who respect the vaccinal calendar.To spicify factors limiting the access of these children to the vaccinationTo propose the strategies to make agreat deal of these infants to the respect of the vaccinal calendar  The descriptive transversal, ethod has served to the realization of the recherch followed by the direct trace of BCG scar at thefoream of each child. Furthermore we have checed the vaccination form fo each kid. The main results below have been noted or listed :100% of pygmy children did not respect the vaccination calender94 % of pygmy kids did not have the BCG scar at the left forearm100% of these pygmy children had nod the CPS form16% of the investigated infants were in the 25 to 29 weeks of age-group3 of the pygmy kids are borna t the maternity hospital43% of these pygmy children’s mothers indicate by ignorencethe deltoid muscle as the site or place of the BCG vaccine injection60% of caises had a namber of 3 to 5 pygmy infants41% of pygmy sensititess were nurses.The pygmy children are ot vaccinated  in Isiro and its surrounndings. The congolese government through its minister of public health must initiate  the autchonous pygmypeople’s itegration programme in the sensitization in ordeer to accept the vaccine to avoid these mortal diseases. This alson necessitates te participation of international and national organizations for the success of the investigation of pygymies’ health activities in its totality.